Concurrent waterlogging and anthracnose-twister disease in rainy-season onions (Allium cepa): Impact and management - Salunkhe, Vanita Navnath; Gedam, Pranjali; Pradhan, Aliza; Gaikwad, Bhaskar; Kale, Rajiv; Gawande, Suresh (Frontiers in Microbiology, 2022)
Waterlogging and anthracnose-twister disease are serious constraints in rainy season onion cultivation. Being a shallow-rooted crop, onion is highly sensitive to waterlogging. In addition to waterlogging, anthracnose-twister disease complex is also prevalent across the world, wherever rainy season onion cultivation has been taken. Waterlogging is the major predisposing factor for anthracnose and other fungal diseases. However, studies on combined stress impact on onion has been ignored. In present review, we have presented the overview of the anthracnose-twister disease, waterlogging effect on host physiology, host-pathogen interaction under waterlogging stress, and appropriate management strategies to mitigate the combined stress effects. Crucial soil and crop management strategies can help to cope with the negative impact of concurrent stresses. Raised bed planting with drip irrigation, use of plant bio-regulators along with nutrient management, and need-based fungicide sprays would be the most reliable and feasible management options. Genetic improvement of commercial onion cultivars would be the most comprehensive solution to endure combined stress impact.